Supercapacitive performance of ionic-liquid-intercalated two-dimensional Ti3C2Tx in redox electrolyte - Jadhav, Ashwini (Cell Press, 2025)
Two-dimensional (2D)-Ti3C2Tx is a promising candidate for supercapacitors; however, it undergoes irreversible oxidation in aqueous acidic electrolytes at a higher anodic potential. Here, we enhance the supercapacitive performance of Ti3C2Tx in the potential range of 0–1 V by a suitable combination of intercalating molecules (for example, EmBF4 [1-ethyl-3-methylimidazolium] and BmBF4 [1-butyl-3-methylimidazolium] tetrafluoroborate) and redox electrolytes (for example, H2SO4 plus KI). Pristine Ti3C2Tx, Em-intercalated Ti3C2Tx (Ti3C2Tx-Em), and Bm-intercalated Ti3C2Tx (Ti3C2Tx-Bm) are utilized for supercapacitor applications and show low capacitance and poor stability in 1 M H2SO4. Interestingly, Ti3C2Tx, Ti3C2Tx-Em, and Ti3C2Tx-Bm supercapacitors exhibit improved performance in redox electrolyte. In particular, Ti3C2Tx-Em demonstrates gravimetric capacitance of 725 Fg−1 and >90% capacitance retention after 10,000 cycles. We attribute this high performance to (1) the higher interlayer spacing of Ti3C2Tx-ionic liquids and (2) effective interaction of the redox pair with the Ti3C2Tx-Em framework. Our findings suggest that incorporating anodic redox pairs into aqueous acidic electrolytes is a valuable strategy to improve the performance of Ti3C2Tx electrodes.